Persepsi Pengunjung terhadap Kualitas Ruang Terbuka Publik di Kota Makassar - Jeane Claudia Mandy; Ananto Yudono; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Public space is used by the community as a place for social interaction and sports of various ages from children to adults. Lapangan Emmy Saelan has functions, including as a means of recreation and sports, the lungs of the city, balancing urban life, and places where people socialize. In terms of the use of space, public open space should have a decent quality in terms of the availability of facilities and supporting elements, so that people will feel safe and comfortable in their activities. This study aims to identify visitors’ perceptions of the quality of public open spaces in Lapangan Emmy Saelan, identify factors that influence the frequency of community visits to the public open space of Lapangan Emmy Saelan, providing direction for development in improving the quality of public open spaces at Lapangan Emmy Saelan. The analytical methods used is analysis of Importance Performance Analysis (IPA) and Spearman correlation analysis. The results of this study by considering variables based on accessibility, comfort, activity, and sociability, it can be concluded that in general the quality of the public open space of the Lapangan Emmy Saelan is low quality. In addition, the factors that influence the frequency of community visits to public open spaces include limited accessibility, especially for visitors with special needs, limited children's play facilities, and sports facilities both in number and quality. Directions are taken to improve the quality of public space by developing the attributes found in the first quadrant of the science matrix.